A time series analysis of the retail prices of regular and well milled rice in Iloilo, Philippines 1985-89. - Jusayan, Jude Anthon (1991.)
In the country, the price of rice left alone to the forces of demand and supply, is subject to large and episodic fluctuation through time. This can be detrimental to both rice farmers and consumers. Low price of palay may lead to low income for farmers while high rice prices may erode the consumers' purchasing power. This paper presents the time series analysis of the monthly retail prices of regular and well milled rice in Iloilo from 1985 to 1989. The period covered includes sixty observations., The study showed that the seasonality of both rice prices behaved similarly. Rice prices were below average from October to January and above average from May to September. Both rice prices registered the lowest seasonality in the month of December, and the highest in the month of August. A trend analysis revealed that the monthly growth rate of the retail price of regular milled rice was 0.52 and 0.55 for well milled rice. The cyclical component for both rice prices move similarly. The cyclical component showed that in 1985, both rice prices experienced a down swing. In 1986 until 1988, rice prices were leveling. In 1989, both rice prices started cyclical upswing. Furthermore, the study revealed that rice prices in 1987 and 1989 were relatively higher, because of high irregularities found in those years. The forecasting of the monthly rice prices for 1990 and 1991 using a simple exponential smoothing model based on the multiplicative time series model was successful. The study suggests that a structural analysis of the retail price of both kind of rice be pursued. The forecasting method used in this research can also be applied in forecasting future prices of other basic commodities.
Thesis (Undergraduate, Bachelor of Arts in Economics) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Well Milled Rice -- Price